1999
DOI: 10.1001/archopht.117.5.649
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Topical Ascorbic Acid on Free Radical Tissue Damage and Inflammatory Cell Influx in the Cornea After Excimer Laser Corneal Surgery

Abstract: To evaluate the effect of topical ascorbic acid on oxygen free radical tissue damage and the inflammatory cell influx in the cornea after excimer laser keratectomy.Methods: Five New Zealand white rabbits underwent bilateral phototherapeutic keratectomy with the 193-nm argon fluoride excimer laser. Following treatment, the right eye of each rabbit was treated with 10% ascorbic acid every 3 hours for 24 hours. The left eyes served as controls. After 24 hours, all animals were killed and their corneas were trephi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
74
0
5

Year Published

2002
2002
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 77 publications
(81 citation statements)
references
References 25 publications
2
74
0
5
Order By: Relevance
“…Since corneal damage during inflammation is characterized by monocytes/macrophages and neutrophils invasion that can release ROS, proteolytic enzymes and arachidonic acid [25,60,62]. The indirect anti-inflammatory effect of pirenoxine and melatonin, dependent on their scavenger activities, can counteract several deleterious effects of inflammation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Since corneal damage during inflammation is characterized by monocytes/macrophages and neutrophils invasion that can release ROS, proteolytic enzymes and arachidonic acid [25,60,62]. The indirect anti-inflammatory effect of pirenoxine and melatonin, dependent on their scavenger activities, can counteract several deleterious effects of inflammation.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, physiological scavenging agents, such as superoxide dismutase (SOD), catalase, vitamin E, glutathione, ascorbic acid, as well as steroidal or non-steroidal anti-inflammatory molecules, have been tested in order to inhibit the harmful action of UV-B radiation or the side effects of excimer laser therapy on the cornea [20][21][22][23][24][25].…”
Section: Introductionmentioning
confidence: 99%
“…ROS induce the peroxidation of fatty acids or lipids and proteins of the cell membranes, degrade corneal stromal tissue by scission of covalent bonds or enhancing their susceptibility to hydrolytic enzymes. 7,11 Previous studies have demonstrated that excimer laser keratectomy increases the corneal temperature, decreases the superoxide dismutase activity of the aqueous humour, and induces lipid peroxidation in the superficial corneal stroma. 7,8 Excimer laser treatment also changes the corneal activities of aldehyde dehydrogenase and glutathione S-transferase, these two enzymes play an important role in detoxification of aldehydes, which are generated from free radical reactions.…”
Section: Discussionmentioning
confidence: 99%
“…[6][7][8][9][10] The harmful effects of reactive oxygen species (ROS) are widely known, and the pharmacological treatments to reduce oxidative damage in corneal tissue after PRK is under investigation. 11,12 Superoxide dismutase (SOD) and glutathione peroxidase Eye (Gpx) are the main antioxidant enzymes which protect the cornea from radical injury. 13,14 Catalase which has little activity in the cornea is another antioxidant enzyme of it.…”
mentioning
confidence: 99%
“…Since previous studies suggest the use of antioxidant enzymes and scavenger molecules to prevent the production of free radicals or neutralize their toxic action [28][29][30][31], the effectiveness of the scavenging molecule pirenoxine was tested contemporaneously.…”
Section: Introductionmentioning
confidence: 99%